5. KEKERASAN BERNUANSA KEAGAMAAN DAN POLITIK - Marom, Aufarul (Faculty of Social and Political Sciences Diponegoro University, 2008)
Radical Attitude and Relio-Radicalism born from unequality of power, competion and injustice action of government or injustice of majority to minority produce violence. Violence appeared from Radical Socio-Religion’s Group tends to destructive movement. Destructive violence acted by Radical Sosio-Relion’s Group has happened in political domain. The problem is how to anticipation and eliminated their destructive movement.